GROW ORGANIC, EAT ORGANIC: A STEP TOWARDS SUSTAINABLE AGRICULTURE - Priyanka Jalal, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
A real challenge for sustainable development in the modern era is the growing population across the world and to meet their demands, farmers are using modern farming practices (such as the use of pesticides, synthetic fertilizers, Stubble burning etc. to enhance crop output). These are causing several problems such as depletion of soil health, climatic changes, drop in river water and ground water table, increases pollution and health diseases like cancer, blood pressure, fragile bones and skin diseases etc. Therefore, GOs and NGOs are taking initiative to promote organic farming practices and aware the people about the excessive use of fertilizers. Organic agriculture is a productive and promising agricultural strategy for environmental sustainability. As it improves soil fertility, eliminates environmental issues and reduces the need of synthetic fertilizers. Meanwhile, this type of agriculture encourages sustainable, long-term economic growth. Rural women are also an integral part of Indian agricultural system so it is important to ensure their involvement in natural resource management and adaptation of organic farming practices as well. Thus, it is suggested to provide trainings to farmers, organize campaigns/ awareness programmes related to organic agriculture.